2006
DOI: 10.1111/j.1600-0838.2006.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Customer‐oriented counseling for physical activity in older people: study protocol and selected baseline results of a randomized‐controlled trial (ISRCTN 07330512)

Abstract: The objective of this study is to describe the rationale, design and selected baseline results of a 2-year randomized-controlled trial (RCT) on the effects of physical activity counseling in community-living older people. After a four-phase screening and data-collection process targeting all independently living people in the city center of Jyväskylä, Finland, six hundred and thirty-two 75-81-year-old cognitively intact, sedentary persons who were able to move independently outdoors at least minimally and will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…One possible explanation for given results could be attributed to the positive effect of walking on cardiovascular fitness, stress control, and weight control (2). Consistent with our study, Leinonen et al, and Chodzko-Zajko l suggested that regular aerobic exercise improves the quality of life in older adults (14,15). Furthermore, Brach et al showed that daily exercise with medium intensity (20 -30 minutes) contributes to reduce activity limitations, increase role-playing, and hence, increase the quality of life and well-being among the aged persons (16).…”
Section: Discussionsupporting
confidence: 87%
“…One possible explanation for given results could be attributed to the positive effect of walking on cardiovascular fitness, stress control, and weight control (2). Consistent with our study, Leinonen et al, and Chodzko-Zajko l suggested that regular aerobic exercise improves the quality of life in older adults (14,15). Furthermore, Brach et al showed that daily exercise with medium intensity (20 -30 minutes) contributes to reduce activity limitations, increase role-playing, and hence, increase the quality of life and well-being among the aged persons (16).…”
Section: Discussionsupporting
confidence: 87%
“…The original list consisted of 24 constraints on physical exercise [15]. All different constraints listed here showed a good reliability (κ=0.417-1.00) among the persons screened in Finland aged 75-81 [16]. Our data confirmed a satisfactory internal consistency and good construct validity of the scale and suitability for population-based screening purposes.…”
Section: Discussionsupporting
confidence: 60%
“…20 SCAMOB was a 2-year, single-blind, randomized controlled trial on the effects of individualized physical activity counseling on older sedentary people. The intervention took place in the city of Jyvä skylä located in central Finland with a population of 82,000 inhabitants, of whom 6.1% were aged 75 and older.…”
Section: Design and Settingmentioning
confidence: 99%